2018
DOI: 10.1016/j.ijsu.2018.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin dose affects the fate of hepatic ischemia and reperfusion injury in rats: An experimental research

Abstract: Quercetin can be effective in preventing of hepatic I/R injury when the correct dose was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…Our study demonstrated that the hepatic ischemia for 30 min followed by 30 min of reperfusion led to liver injury as evidenced by significant elevation of liver enzymes, ALT, and AST, levels which indicating hepatocytes damage. These results are in accordance with previous studies (Mard et al, ; Uylas et al, ). Moreover, these effects were supported by the histological changes observed in IR rats in the form of perivascular edema, few areas of focal hemorrhage, vacuolar degeneration, and swelling of hepatocytes, with nuclear condensation, pyknosis, fragmentation, and signs of cellular necrosis.…”
Section: Discussionsupporting
confidence: 94%
“…Our study demonstrated that the hepatic ischemia for 30 min followed by 30 min of reperfusion led to liver injury as evidenced by significant elevation of liver enzymes, ALT, and AST, levels which indicating hepatocytes damage. These results are in accordance with previous studies (Mard et al, ; Uylas et al, ). Moreover, these effects were supported by the histological changes observed in IR rats in the form of perivascular edema, few areas of focal hemorrhage, vacuolar degeneration, and swelling of hepatocytes, with nuclear condensation, pyknosis, fragmentation, and signs of cellular necrosis.…”
Section: Discussionsupporting
confidence: 94%
“…The effects of Liv-52 on the liver damage induced by I/R were also examined histopathologically in our study. It's shown that I/R application causes degeneration in hepatocyte, vein and intercellular edema and congested sinusoidal damage in the rat liver [32]. It has also been reported that, by the application of Liv-52, hepatocytes become normal histopathologically in the cadmiuminduced hepatic toxicity and Liv-52 reverses cadmiuminduced hepatic damage [33].…”
Section: Discussionmentioning
confidence: 99%
“…The rats in Group 2 (post-burn group) were administered 1 ml of DMSO, intraperitoneally, every day for 7 days, before the burn procedure and 50 mg/kg of quercetin in 1 ml of DMSO, intraperitoneally, every day after the burn procedure until euthanasia was performed (10).…”
Section: Methodsmentioning
confidence: 99%
“…The rats in Group 3 (pre-burn group) were administered 50 mg/ kg of quercetin in 1 ml of DMSO, intraperitoneally, every day for 7 days before and after the burn procedure until euthanasia was performed (10).…”
Section: Methodsmentioning
confidence: 99%